Enhancing Readiness Trough Economic Literacy: A Study of Prospective Economics Teachers - Putri, Salma Nabila; Wulandari, Wida (PT. Maju Malaqbi Makkarana, 2025)
Education is an important aspect of human life that relies heavily on the role of teachers as the main factor in the success of the educational process. Professional teachers are formed through careful preparation from an early age, one of which is through an education study program in college. Economics education students are specifically prepared to become economics teachers in the future. Their readiness is influenced by the mastery of knowledge in their field of study and teaching experience through direct practice. This study aims to determine the effect of economic literacy on the readiness of students to become teachers. The analysis method used is linear regression. Quantitative approach using SPSS with 86 respondents. The results showed that economic literacy has a significant effect on readiness to become a teacher.